A method for preparing a high transparent barrier coating for plastic packaging
Patent Information
- Application Number
- CN202511845231.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-09
AI Technical Summary
[0006]本发明的目的是提供一种塑料包装的高透明阻隔涂层的制备方法,解决了传统塑料包装涂层阻隔性与透明性难兼顾、附着力弱、湿热稳定性差的行业痛点:通过纳米填料的化学杂化与精准工艺调控,既让涂层形成致密阻隔结构以阻挡气体与水汽渗透,又保持了高透明外观;搭配适配性交联剂与基材预处理,强化了涂层与基材的结合力,在高温湿热环境下仍能维持稳定性能;同时以水性体系、低填料用量兼顾了环保性与成本优势,可适配食品、医药等高要求包装场景
(1)通过钠基蒙脱土酸性活化、纳米微晶纤维素化学杂化制备HNF分散液,填料以100-250nm粒径均匀分散,形成致密片层阻隔结构(氧气透过率低至2.8cm3/(m2·d·atm)),同时保持透光率≥93%、雾度≤0.9%,满足高透明包装需求;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of barrier coating preparation technology, and in particular to a method for preparing a highly transparent barrier coating for plastic packaging. Background Technology
[0002] Food packaging, especially for the preservation of fresh fruits and vegetables (such as corn), has extremely stringent requirements for oxygen barrier properties. In order to extend shelf life, the market requires packaging materials to have high transparency (to meet display needs) and extremely high oxygen barrier capabilities.
[0003] The mainstream technologies for achieving high-barrier packaging currently available have the following inherent drawbacks: Multilayer co-extruded films (such as EVOH-based films): These are produced by multilayer co-extrusion using ethylene-vinyl alcohol copolymer (EVOH) as a barrier layer. While this method offers excellent barrier properties, it suffers from three major drawbacks: High humidity sensitivity: The barrier properties of EVOH decrease sharply under high temperature and humidity conditions, which is typical of the environment inside many fresh food packaging bags. High cost and complexity: Multi-layer co-extrusion equipment is expensive, and the production process is complex and lengthy. Difficult recycling: The multi-layer heterogeneous material structure makes it difficult to separate and recycle, which does not meet the requirements of sustainable development.
[0004] Traditional barrier coatings: Polyvinylidene chloride (PVDC) coating: Although it has good barrier properties, it may pose environmental risks due to chlorine compounds during production and use, and its combustion can produce dioxins, raising concerns about its environmental performance.
[0005] silicon dioxide (SiO) x Evaporated coatings require huge equipment investment and have high production costs; moreover, the vapor-deposited coating is essentially an inorganic ceramic material with poor flexibility, which is prone to micro-cracks when bent or rubbed, leading to failure of barrier performance. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a highly transparent barrier coating for plastic packaging, which solves the industry pain points of traditional plastic packaging coatings, such as difficulty in achieving both barrier properties and transparency, weak adhesion, and poor stability under humid and hot conditions. By using chemical hybridization of nanofillers and precise process control, the coating forms a dense barrier structure to block gas and moisture penetration while maintaining a highly transparent appearance. Combined with a compatible crosslinking agent and substrate pretreatment, the adhesion between the coating and the substrate is strengthened, and the coating can maintain stable performance under high temperature and humid and hot conditions. At the same time, the water-based system and low filler dosage take into account both environmental protection and cost advantages, making it suitable for high-requirement packaging scenarios such as food and pharmaceuticals.
[0007] To achieve the above objectives, the present invention provides a method for preparing a highly transparent barrier coating for plastic packaging, comprising the following steps: S1. A hybrid nanofiller dispersion was prepared by hybridizing sodium-based montmorillonite. S2. The hybrid nanofiller dispersion prepared in S1 is mixed with an aqueous polyurethane dispersion, an oxazoline crosslinking agent, a wetting and leveling agent and an antifoaming agent to prepare a coating liquid. S3. Apply, cure, roll up and mature the coating liquid obtained in S2 to obtain a highly transparent barrier coating.
[0008] Preferably, the specific operation of S1 is as follows: S11, sodium-based montmorillonite acid activation: Sodium montmorillonite dispersion was placed in a flask, pH was adjusted, and then silane coupling agent diluted with anhydrous ethanol was added. The mixture was then heated and stirred to activate the sodium montmorillonite dispersion. S12. Place the nanocrystalline cellulose dispersion in a dispersion tank, start the high-speed shear disperser, and add the activated sodium montmorillonite dispersion obtained in S11 dropwise into the dispersion tank. After the dropwise addition is completed, raise the temperature and continue shearing and stirring to carry out the hybridization reaction. S13. After the hybridization reaction is completed, adjust the pH with an alkaline solution and continue stirring to obtain the HNF primary dispersion. S14. The HNF primary dispersion obtained in S13 is centrifuged and concentrated to obtain a concentrated paste. The concentrated paste is then subjected to ultrasonic homogenization to obtain a hybrid nanofiller dispersion, denoted as HNF dispersion.
[0009] Preferably, in S11, the silane coupling agent is KH-560, the concentration of sodium montmorillonite dispersion is 1-3 wt%, the pH is adjusted to 4-5, the volume of anhydrous ethanol is 0.5-2 times the volume of sodium montmorillonite dispersion, the dropping rate of silane coupling agent dispersion is 3-8 mL / min, the temperature is raised to 55-65℃, the stirring speed is 400-600 rpm, and the stirring time is 60-120 min; The mass of the silane coupling agent is 4-8% of the total dry weight of the sodium-based montmorillonite dispersion and the dry weight of the nanocrystalline cellulose dispersion.
[0010] Preferably, in S12, the concentration of the nanocrystalline cellulose dispersion is 1-3 wt%, the dry weight ratio of the nanocrystalline cellulose dispersion to the dry weight of the sodium montmorillonite dispersion in S11 is 1:1, the shearing and stirring speed is 6000-10000 rpm, the shearing time is 10-20 min, the dropping rate of the activated sodium montmorillonite dispersion is 5-15 mL / min, the temperature of the hybridization reaction is 70-80℃, the stirring speed is 200-400 rpm, and the stirring time is 3-5 h.
[0011] Preferably, in S13, the pH is adjusted to 6.5-7.5 and stirred for 20-40 minutes.
[0012] Preferably, in S14, the solid content of the concentrated paste is 8-10%, the ultrasonic energy input is 15-35kJ / L, and the solid content of the HNF dispersion obtained after ultrasonic homogenization is 4-6%, the viscosity is <250mPa·s, the Zeta potential is ≤-30mV, and the dispersed particle size is 100-250nm.
[0013] Preferably, the specific operation of S2 is as follows: the aqueous polyurethane dispersion is placed in a mixing tank, then the HNF dispersion obtained in S14 is added dropwise to the mixing tank and stirred, then the wetting and leveling agent, defoamer and deionized water are added in sequence and stirred, and finally the oxazoline crosslinking agent is added and stirred to obtain the coating liquid.
[0014] Preferably, in S2, the dry weight of each component is as follows, by weight fraction: 88-95% aqueous polyurethane dispersion, 3-8% HNF dispersion, 1-4% oxazoline crosslinking agent, 0.1-0.5% wetting and leveling agent, 0.1-0.3% defoamer, and the remainder is deionized water; When adding HNF dispersion, the stirring speed is 300-500 rpm and the stirring time is 20-40 min. After adding wetting and leveling agent, defoamer and deionized water, stir at 300-500 rpm for 20-40 min and control the viscosity to stabilize at 150-200 mPa·s. When adding oxazoline crosslinking agent, the stirring speed is 150-200 rpm and the stirring time is 10-20 min.
[0015] Furthermore, the wetting and leveling agent is an organosilicon, the defoamer is a polyether-modified organosilicon, the oxazoline crosslinking agent is an oxazoline-based water-soluble polymer, and the waterborne polyurethane dispersion is an aliphatic waterborne polyurethane dispersion.
[0016] Preferably, the specific operation of S3 is as follows: pre-treating the substrate, then applying the coating liquid onto the pre-treated substrate; after coating, performing gradient hot air curing; after curing, performing winding and aging to finally complete the preparation of the coating.
[0017] Preferably, in S3, the substrate is a heat-resistant BOPP film with a thickness of 20-30μm, a heat distortion temperature ≥120℃, a tensile strength ≥25MPa, and an initial surface tension ≤32mN / m; The substrate is subjected to atmospheric plasma treatment with a power of 400-600W, using air as the medium and a speed of 100-150m / min. The surface tension of the film after treatment is 46-52mN / m, and the coating is completed within 1-4 hours. Coating is performed using an anilox roller with a density of 100-150 lines per inch and a volume of 8-12 cm³. 3 / m 2The coating process is carried out at a roller pressure of 0.1-0.2 MPa and a coating speed of 80-150 m / min, with a dry coating weight of 1.5-2.2 g / m. 2 ; Gradient hot air curing is divided into a drying section and a curing section. In the drying section, the temperature is 80-95℃, the wind speed is 4-10m / s, and the time is 30-60s. In the curing section, the temperature is 100-115℃, the wind speed is 6-10m / s, the time is 60-100s, and the outlet film surface temperature is 95-110℃. The winding tension is 40-70N, and the product is cured for 10-30 hours at 20-30℃ and 40-60% relative humidity.
[0018] Therefore, the present invention employs the above-mentioned method for preparing a high-transparency barrier coating for plastic packaging, which has the following beneficial effects: (1) HNF dispersion was prepared by acid activation of sodium montmorillonite and chemical hybridization of nanocrystalline cellulose. The filler was uniformly dispersed with a particle size of 100-250 nm to form a dense lamellar barrier structure (oxygen permeability as low as 2.8 cm). 3 / (m 2 (·d·atm)), while maintaining a light transmittance of ≥93% and a haze of ≤0.9%, to meet the requirements for high-transparency packaging; (2) The surface tension of the substrate is increased to 46-52mN / m by atmospheric plasma pretreatment. Combined with the stable cross-linking of oxazoline cross-linking agent with water-based polyurethane and HNF, the coating adhesion reaches grade 0. After boiling at 121℃, the oxygen permeability retention rate is ≥90%, and the water resistance is free from whitening and peeling, making it suitable for high-temperature sterilization packaging scenarios. (3) The pH is precisely controlled throughout the process (activation pH=4.5, neutralization pH=7.0), and with ultrasonic homogenization, the Zeta potential of the HNF dispersion is ≤-30mV, and the dispersibility is excellent; the process parameters (such as HNF dosage and hybridization temperature) are tolerant, and the performance is stable during batch production; (4) It adopts an aqueous system (without organic solvents), which meets the environmental protection requirements of packaging materials; the amount of hybrid filler is only 3-8%, and high barrier can be achieved without high addition amount, reducing raw material cost.
[0019] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation
[0020] The technical solution of the present invention will be further described below through embodiments.
[0021] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0022] Example 1 This invention provides a method for preparing a highly transparent barrier coating for plastic packaging, comprising the following steps: S1: Preparation of HNF dispersion: S11, MMT Acid Activation: Take 1000g of a 2.0wt% sodium montmorillonite (MMT) dispersion (20g dry weight) and place it in a 2L four-necked flask. Adjust the pH to 4.5 with 0.1M acetic acid solution. Dilute 1.2g of KH-560 (6% of the total dry weight of subsequent MMT and NCC) with 1.2mL of anhydrous ethanol and add it dropwise to the system at a rate of 5mL / min. Heat to 60℃ and activate with stirring at 500rpm for 90min, maintaining pH=4.5 throughout the process.
[0023] S12, High-speed shear hybridization: Take 1000g of 2.0wt% (NCC) dispersion (20g dry weight) and place it in a 3L dispersion vessel. Perform high-speed shearing at 8000rpm. Add the activated MMT dispersion dropwise at a rate of 10mL / min. After the addition is complete, continue shearing for 15min.
[0024] S13. Isothermal reaction and neutralization: The mixture was transferred to a 5L reactor and reacted at 75℃ and 300rpm for 4 hours. After the reaction was completed, the pH was adjusted to 7.0 with 0.1M ammonia water and stirred for 30 minutes to obtain the primary dispersion of HNF.
[0025] S14. Concentration and Homogenization: The primary HNF dispersion was centrifuged to obtain a concentrated paste with a solid content of approximately 9%. The concentrated paste was ultrasonically treated (energy input 25 kJ / L), and water was added to adjust the solid content to 5.0% to obtain an HNF dispersion. The viscosity of the HNF dispersion was measured to be 180 mPa·s, the Zeta potential to be -38 mV, and the dispersed particle size to be 165 nm.
[0026] S2: Preparation of coating liquid: Dry weight formulation: 92% waterborne polyurethane dispersion (WPU), 5% HNF dispersion, 2% oxazoline crosslinking agent, 0.3% wetting and leveling agent, 0.2% defoamer, and 0.5% deionized water.
[0027] Procedure: Add 2628.6g of WPU (35% solids, 920g dry weight) to a mixing tank. Slowly add 1000g of HNF dispersion (5% solids, 50g dry weight) dropwise at 400rpm, stirring for 30min after the addition is complete. Then add 3g of wetting and leveling agent, 2g of defoamer, and 5g of deionized water sequentially, continuing stirring for another 30min. The viscosity was measured to be 170mPa·s. 30min before coating, add 50g of oxazoline crosslinking agent (40% solids, 20g dry weight) at 200rpm, stirring for 15min.
[0028] S3: Coating and Curing: Substrate: Heat-resistant BOPP film (25μm thickness, heat distortion temperature ≥120℃) is used, which is treated with 500W atmospheric plasma. The surface tension after treatment is 50mN / m, and the coating is completed within 2 hours.
[0029] Coating: Using a 130 line / inch anilox roller, coating was applied at a roller pressure of 0.15 MPa and a speed of 120 m / min, with the dry coating weight controlled at 1.8 g / m². 2 .
[0030] Curing: Drying section 85℃, air velocity 7m / s, time 40s; Curing section 105℃, air velocity 8m / s, time 80s. Outlet film temperature 102℃.
[0031] Curing: Curing at 25℃ and 50% relative humidity for 24 hours finally yields a highly transparent barrier coating.
[0032] Example 2 The only difference between this embodiment and Embodiment 1 is that in the coating liquid formulation of S2, the dry weight addition of HNF is 4%, and the dry weight ratio of WPU is adjusted to 93% accordingly. All other conditions are the same.
[0033] Example 3 The only difference between this embodiment and Embodiment 1 is that the isothermal reaction temperature in the hybridization reaction of S13 is 72°C, while all other conditions are the same.
[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that no pH adjustment was performed during the MMT acid activation of S11 and throughout the entire subsequent S1 process (the system maintained an initial neutral environment with a pH of approximately 6.5), while all other conditions remained the same.
[0035] Comparative Example 2 The only difference between this comparative example and Example 1 is that S1 uses a simple physical blending method: that is, without acid activation-hybridization reaction, MMT dispersion and NCC dispersion of the same dry weight (20g) are directly subjected to high-speed shearing at 8000rpm for 15min without the addition of KH-560, and then the coating liquid is prepared with WPU and other raw materials in the same proportion. All other conditions are the same.
[0036] Comparative Example 3 The only difference between this comparative example and Example 1 is that, in step S2, an aziridine crosslinking agent with equimolar crosslinking functional groups was used instead of an oxazoline crosslinking agent; all other conditions were the same.
[0037] The coatings prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests: Oxygen transmission rate (OTR, 23℃, 90% RH): The test standard is ASTM D3985-2017: Determination of oxygen transmission rate in plastic films and sheets; Water vapor transmission rate: The test standard is ASTM E96, "Standard Test Method for Water Vapor Transmission Rate (WVTR) of Materials"; Optical performance: The test standard for transmittance and haze is ASTM D1003-2013 "Transparent plastics, test method for transmittance and haze"; Adhesion: The test standard is ASTM D3359 "Adhesion Test Standard"; Water resistance: The test method is as follows: the coating sample is completely immersed in deionized water and soaked at room temperature for 24 hours. After soaking, the sample is taken out and the surface moisture is dried with filter paper. The coating is observed to see if whitening, bubbles, wrinkles and peeling occur, and is compared with the sample before soaking. Resistant to boiling: The test method is as follows: Place the coated sample in an autoclave, ensuring it does not directly contact the inner metal wall. Set the program, raise the temperature and pressure to 121±1℃ and 0.12MPa, and hold the pressure for 30 minutes. After the program ends, allow it to cool naturally to room temperature. Remove the coated sample and calculate the ratio of the OTR value after the boiling test to the OTR value before boiling, expressed as retention rate (%). The higher the retention rate, the better the wet heat stability of the coating.
[0038] The test results are shown in Table 1.
[0039] Table 1 Performance Test Results
[0040] As shown in Table 1, the light transmittance of Examples 1-3 is all >93%, and the haze is <1%, indicating that the coating has excellent optical transparency and hardly affects the visual effect of the packaging material. This is due to the successful pH-controlled in-situ hybridization. The formed HNF (hybrid nanofiller) achieves uniform dispersion at the nanoscale in the WPU matrix, avoiding light scattering caused by filler agglomeration, thus ensuring extremely high transparency while introducing a highly efficient barrier network.
[0041] Comparative Example 2 exhibited a haze as high as 3.8% and the lowest transparency. This directly demonstrates the crucial role of in-situ hybridization in preventing nanoparticle aggregation and maintaining high transparency, an effect that simple physical mixing cannot achieve.
[0042] Under harsh conditions of 23°C and 90% RH, the OTR of Example 1 was as low as 2.8, while Examples 2 and 3 also remained below 5. The comparative example had an OTR as high as 16.5, with a sharp decline in performance, demonstrating that pH regulation is an indispensable core step in constructing efficient hybrid networks, and its contribution is not obvious.
[0043] Comparative Example 2 had an OTR of 9.3, significantly lower than the Example, demonstrating the disruptive advantage of in-situ hybridization over simple blending in constructing highly efficient barrier structures. The mechanism is as follows: In HNF, NCC fibers and MMT sheets are covalently linked, forming a dense nano-brick wall structure that greatly extends the diffusion path of oxygen molecules. Simultaneously, pH regulation ensures the integrity and stability of the hybrid structure, making it less susceptible to damage under high humidity conditions.
[0044] The adhesion of Examples 1-3 was all at the optimal level 0, and the water resistance remained unchanged. This indicates that the coating is firmly bonded to the substrate and has a dense cross-linked structure, which can effectively resist moisture erosion. The OTR retention rate of Examples 1-3 was all >89%, proving that the coating can withstand high temperature and high pressure sterilization treatment and is suitable for food packaging fields that require cooking sterilization.
[0045] Comparative Examples 1 and 2 showed poor performance in both water resistance and boiling resistance, further confirming that incomplete hybrid networks and poor interfacial compatibility severely weaken the durability of the coating. The boiling resistance retention rate of Comparative Example 3 was only 72%, significantly lower than the 91% of Example 1. This strongly demonstrates a unique synergistic effect between the oxazoline crosslinking agent and the HNF / WPU system, enabling the formation of a more stable and resistant crosslinking network to humid heat aging.
[0046] Therefore, the present invention adopts the above-mentioned method for preparing a high-transparency barrier coating for plastic packaging, which solves the industry pain points of traditional plastic packaging coatings, such as difficulty in achieving both barrier and transparency, weak adhesion, and poor humid heat stability. Through the chemical hybridization of nanofillers and precise process control, the coating forms a dense barrier structure to block gas and water vapor penetration while maintaining a high-transparency appearance. Combined with a compatible crosslinking agent and substrate pretreatment, the bonding force between the coating and the substrate is strengthened, and the stable performance can still be maintained in high-temperature and humid heat environments. At the same time, the water-based system and low filler dosage take into account both environmental protection and cost advantages, making it suitable for high-requirement packaging scenarios such as food and pharmaceuticals.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a highly transparent barrier coating for plastic packaging, characterized in that: Includes the following steps: S1. A hybrid nanofiller dispersion was prepared by hybridizing sodium-based montmorillonite. The specific operation of S1 is as follows: S11, sodium-based montmorillonite acid activation: Sodium montmorillonite dispersion was placed in a flask, pH was adjusted, and then silane coupling agent diluted with anhydrous ethanol was added. The mixture was then heated and stirred to activate the sodium montmorillonite dispersion. S12. Place the nanocrystalline cellulose dispersion in a dispersion tank, start the high-speed shear disperser, and add the activated sodium montmorillonite dispersion obtained in S11 dropwise into the dispersion tank. After the dropwise addition is completed, raise the temperature and continue shearing and stirring to carry out the hybridization reaction. S13. After the hybridization reaction is completed, adjust the pH with an alkaline solution and continue stirring to obtain the HNF primary dispersion. S14. The HNF primary dispersion obtained in S13 is centrifuged and concentrated to obtain a concentrated paste. The concentrated paste is then subjected to ultrasonic homogenization to obtain a hybrid nanofiller dispersion, denoted as HNF dispersion. In S11, the silane coupling agent is KH-560, the concentration of sodium montmorillonite dispersion is 1-3wt%, the pH is adjusted to 4-5, the volume of anhydrous ethanol is 0.5-2 times the volume of sodium montmorillonite dispersion, the dropping rate of silane coupling agent dispersion is 3-8mL / min, the temperature is raised to 55-65℃, the stirring speed is 400-600rpm, and the stirring time is 60-120min; The mass of the silane coupling agent is 4-8% of the total dry weight of the sodium-based montmorillonite dispersion and the dry weight of the nanocrystalline cellulose dispersion; In S12, the concentration of the nanocrystalline cellulose dispersion is 1-3 wt%, the dry weight ratio of the nanocrystalline cellulose dispersion to the dry weight of the sodium montmorillonite dispersion in S11 is 1:1, the shearing and stirring speed is 6000-10000 rpm, the shearing time is 10-20 min, the dropping rate of the activated sodium montmorillonite dispersion is 5-15 mL / min, the temperature of the hybridization reaction is 70-80℃, the stirring speed is 200-400 rpm, and the stirring time is 3-5 h. In S13, adjust the pH to 6.5-7.5 and stir for 20-40 minutes; S2. The hybrid nanofiller dispersion prepared in S1 is mixed with an aqueous polyurethane dispersion, an oxazoline crosslinking agent, a wetting and leveling agent and an antifoaming agent to prepare a coating liquid. S3. Apply, cure, roll up and mature the coating liquid obtained in S2 to obtain a highly transparent barrier coating.
2. The method for preparing a high-transparency barrier coating for plastic packaging according to claim 1, characterized in that: In S14, the solid content of the concentrated paste is 8-10%, the ultrasonic energy input is 15-35kJ / L, and the solid content of the HNF dispersion obtained after ultrasonic homogenization is 4-6%, the viscosity is <250mPa·s, the Zeta potential is ≤-30mV, and the dispersed particle size is 100-250nm.
3. The method for preparing a high-transparency barrier coating for plastic packaging according to claim 1, characterized in that: The specific operation of S2 is as follows: place the aqueous polyurethane dispersion in a mixing tank, then add the HNF dispersion obtained in S14 dropwise into the mixing tank, stir, then add the wetting and leveling agent, defoamer and deionized water in sequence, stir, and finally add the oxazoline crosslinking agent and continue stirring to obtain the coating liquid.
4. The method for preparing a high-transparency barrier coating for plastic packaging according to claim 3, characterized in that: In S2, the dry weight of each component is as follows (by weight fraction): 88-95% aqueous polyurethane dispersion, 3-8% HNF dispersion, 1-4% oxazoline crosslinking agent, 0.1-0.5% wetting and leveling agent, 0.1-0.3% defoamer, and the remainder is deionized water. When adding HNF dispersion, the stirring speed is 300-500 rpm and the stirring time is 20-40 min. After adding wetting and leveling agent, defoamer and deionized water, stir at 300-500 rpm for 20-40 min and control the viscosity to stabilize at 150-200 mPa·s. When adding oxazoline crosslinking agent, the stirring speed is 150-200 rpm and the stirring time is 10-20 min.
5. The method for preparing a high-transparency barrier coating for plastic packaging according to claim 1, characterized in that: The specific operation of S3 is as follows: pre-treat the substrate, and then apply the coating liquid to the pre-treated substrate; After coating, gradient hot air curing is performed. After curing, the coating is rolled up and aged to complete the final coating preparation.
6. The method for preparing a high-transparency barrier coating for plastic packaging according to claim 5, characterized in that: In S3, the substrate is a heat-resistant BOPP film with a thickness of 20-30μm, a heat distortion temperature ≥120℃, a tensile strength ≥25MPa, and an initial surface tension ≤32mN / m; The substrate is subjected to atmospheric plasma treatment with a power of 400-600W, using air as the medium and a speed of 100-150m / min. The surface tension of the film after treatment is 46-52mN / m, and the coating is completed within 1-4 hours. Coating is performed using an anilox roller with a density of 100-150 lines per inch and a volume of 8-12 cm³. 3 / m 2 The coating process is carried out at a roller pressure of 0.1-0.2 MPa and a coating speed of 80-150 m / min, with a dry coating weight of 1.5-2.2 g / m. 2 ; Gradient hot air curing is divided into a drying section and a curing section. In the drying section, the temperature is 80-95℃, the wind speed is 4-10m / s, and the time is 30-60s. In the curing section, the temperature is 100-115℃, the wind speed is 6-10m / s, the time is 60-100s, and the outlet film surface temperature is 95-110℃. The winding tension is 40-70N, and the product is cured for 10-30 hours at 20-30℃ and 40-60% relative humidity.
Citation Information
Patent Citations
Curable resin composition and display element
CN107429030A
Montmorillonoid high-barrier nanometer composite film and preparation method thereof
CN108544826A